Integrated screening of migrants for multiple infectious diseases: Qualitative study of a city-wide programme. (April 2020) - Eborall, Helen; Wobi, Fatimah; Ellis, Kate; Willars, Janet; Abubakar, Ibrahim; Griffiths, Chris; Pareek, Manish
Abstract: Background: Migrants from certain regions are at increased risk of key infectious diseases (including HIV, tuberculosis (TB), hepatitis B and hepatitis C). Although guidelines increasingly recommend integrated screening for multiple infections to reduce morbidity little is known about what migrants and healthcare professionals think about this approach. Methods: Prospective qualitative study in Leicester, United Kingdom within a novel city-wide integrated screening programme in three iterative phases to understand views about infections and integrated screening. Phase 1 focus groups (nine) with migrants from diverse communities ( n  = 74); phase 2 semi-structured interviews with healthcare professionals involved in the screening pathway ( n  = 32); phase 3 semi-structured interviews ( n  = 23) with individuals having tested positive for one/more infections through the programme. Analysis was informed by the constant comparative process and iterative across phases 1–3. Findings: Migrants' awareness of TB, HIV and hepatitis B/C varied, with greater awareness of TB and HIV than hepatitis B/C; perceived susceptibility to the infections was low. The integrated screening programme was well-received by migrants and professionals; concerns were limited to data-sharing. As anticipated, given the target group, language was cited as a challenge but mitigated by various interpretation strategies. Interpretation: This large qualitative analysis is the first to confirm that integrated screening for key infectious diseases is feasible, positively viewed by, and acceptable to, migrants and healthcare professionals. These findings support recent guideline recommendations and therefore have important implications for policy-makers and clinicians as programmes of this type are more widely implemented in diverse settings. Funding: National Institute for Health Research .